Development of Lomustine and n-Propyl Gallate Co-Encapsulated Liposomes for Targeting Glioblastoma Multiforme via Intranasal Administration - Gábor Katona; Fakhara Sabir; Bence Sipos; Muhammad Naveed; Zsuzsanna Schelz; István Zupkó; Ildikó Csóka (MDPI AG, 2022)
This work aimed to develop lomustine (LOM) and n-propyl gallate (PG)-loaded liposomes suitable for targeting glioblastoma multiforme (GBM) via the auspicious nose-to-brain drug delivery pathway. The therapeutical effect of LOM, as a nitrosourea compound, can be potentiated by PG suitable for enhanced anti-cancer therapy. Nose-to-brain delivery of PG and LOM combined in liposomes can overcome the poor water solubility, absorption properties, and toxicity issues in the systemic circulation. Optimization and characterization of the liposomal carrier with binary drug contents were carried out in order to achieve adequate encapsulation efficiency, loading capacity, drug release, and ex vivo permeation. The optimized liposome co-encapsulated with both drugs showed suitable Z-average (127 ± 6.9 nm), size distribution (polydispersity index of 0.142 ± 0.009), zeta potential (−34 ± 1.7 mV), and high encapsulation efficacy (63.57 ± 1.3% of PG and 73.45 ± 2.2% of LOM, respectively) meeting the acceptance criteria of nose-to-brain transport for both drugs. MTT assays of PG-LOM formulations were also conducted on NIH/3T3 (murine embryonic fibroblast), U87 (glioblastoma), and A2780 (ovarian cancer) cell lines indicating reduced an antiproliferative effect on all types of cells. Our results supported the use of this novel combination of LOM and PG in a liposomal formulation as a promising carrier for glioblastoma targeting via the intranasal route.